2005
DOI: 10.1159/000087704
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and Stroke in Centenarians, Okinawa, Japan

Abstract: Objective: To investigate the relationship between a history of hypertension, cigarette smoking and alcohol intake and the lifetime prevalence of stroke in the oldest-old population. Design: A cross-sectional study. Subjects: All of the Japanese centenarians in the Okinawa Prefecture (266 men and 1,378 women). Methods: Okinawa Prefectural Government conducted health surveys among all of the centenarians in Okinawa. The variables used for analysis were sex, history of stroke, age at the first diagnosis of strok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 63 publications
0
5
1
Order By: Relevance
“…Hypertension, smoking, IHD, hypercholesterolemia, atrial fibrillation and diabetes mellitus are the traditional vascular risk factors of stroke, and are of high prevalence in older people [19,20,21,22]. In our study, the prevalence of these vascular risk factors was not significantly different between the stroke cancer and noncancer groups.…”
Section: Discussioncontrasting
confidence: 47%
“…Hypertension, smoking, IHD, hypercholesterolemia, atrial fibrillation and diabetes mellitus are the traditional vascular risk factors of stroke, and are of high prevalence in older people [19,20,21,22]. In our study, the prevalence of these vascular risk factors was not significantly different between the stroke cancer and noncancer groups.…”
Section: Discussioncontrasting
confidence: 47%
“…In comparison with this survey, the prevalence of cerebrovascular disease in centenarians in our study was high. Recently, an Okinawan centenarian study revealed the lifetime prevalence for stroke to be 11.0%; moreover, about two-thirds of such strokes had occurred at 90 years of age (27). The New England Centenarian Study (3) showed the prevalence of stroke in U.S. centenarians to be 14% in men and 15% in women.…”
Section: Presence Of Morbiditymentioning
confidence: 99%
“…Nutrition related factors that have been explored in centenarians include low energy intakes (3), antioxidant status (46), and cardiovascular diseases in centenarians and their offspring (710). We reported in a population-based study of centenarians that the prevalence of vitamin D deficiency was 8.9% (< 25 nmol/L 25-hydroxyvitamin D) and of vitamin D insufficiency was 36.7% (< 50 nmol/L) (2).…”
Section: Introductionmentioning
confidence: 99%